2017
DOI: 10.3171/2017.1.focus16525
|View full text |Cite
|
Sign up to set email alerts
|

Transradial approach for mechanical thrombectomy in anterior circulation large-vessel occlusion

Abstract: OBJECTIVE The goals of this study were to describe the authors' recent institutional experience with the transradial approach to anterior circulation large-vessel occlusions (LVOs) in acute ischemic stroke patients and to report its technical feasibility. METHODS The authors reviewed their institutional database to identify patients who underwent mechanical thrombectomy via a transradial approach over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 16 publications
(20 reference statements)
1
51
1
2
Order By: Relevance
“…A recent study by Chen et al has demonstrated equivalence in efficacy and efficiency between trans-radial and trans-femoral approach for mechanical thrombectomy in anterior circulation stroke,20 and there are reports in the literature of success through the trans-radial approach when a trans-femoral approach has failed 16. Trans-radial is preferred over trans-brachial as the puncture site is easily compressible.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Chen et al has demonstrated equivalence in efficacy and efficiency between trans-radial and trans-femoral approach for mechanical thrombectomy in anterior circulation stroke,20 and there are reports in the literature of success through the trans-radial approach when a trans-femoral approach has failed 16. Trans-radial is preferred over trans-brachial as the puncture site is easily compressible.…”
Section: Discussionmentioning
confidence: 99%
“…The radial artery is relatively superficial, easy to cannulate, and convenient for hemostasis compared with the more challenging transbrachial route. The ease of hemostasis is particularly attractive in the setting of tPA or other coagulopathies, and transradial has been described as a firstline approach in acute ischemic stroke 52. The transbrachial approach offers similar access as the transradial approach in a larger caliber vessel which can then accommodate larger catheters, although hemostasis may be more difficult to achieve.…”
Section: Technical Considerationsmentioning
confidence: 99%
“…Despite significant technological advances, catheterization of the craniocervical arteries can still be challenging. The inability to catheterize the targeted craniocervical vessels via the femoral artery approach has been reported in up to 5% of cases 3 4. The presence of vessel tortuosity and atherosclerosis can increase the complexity and duration of the procedure, and affect the clinical outcome 3 5…”
Section: Discussionmentioning
confidence: 99%